Pinkalicious and the amazing sled run - Kann, Victoria (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2018)
So much snow has fallen in Pinkville that the kids can go sledding from the rooftops, but Pinkalicious' brother Peter is too afraid to sled from such a steep height.
Ages 4-8.
Guided reading level I.
Keywords: Brothers and sisters -- Juvenile fiction; Sledding -- Juvenile fiction; Snow -- Juvenile fiction; Fear -- Juvenile fiction; Brothers and sisters -- Fiction; Sledding -- Fiction; Snow -- Fiction; Fear -- Fiction; JUVENILE FICTION / Readers / Beginner; Readers (Primary); Fiction; Juvenile works; Readers (Publications); Readers (Publications)